Effects of switching from twice-daily tacrolimus to once-daily extended-release meltdose tacrolimus on cellular immune response - Anft, Moritz; Zgoura, Panagiota; Skrzypczyk, Sarah; Dürr, Michael; Viebahn, Richard; Westhoff, Timm H.; Stervbo, Ulrik; Babel, Nina (Frontiers in Transplantation, 2024)
BackgroundLCP-Tacro [LCPT], a novel once-daily, extended-release formulation of tacrolimus, has a reduced Cmax with comparable AUC exposure, requiring a ∼30% dose reduction in contrast to immediate-release tacrolimus (IR-Tac). Once-daily LCPT in de novo kidney transplantation has a comparable efficacy and safety profile to that of IR-Tac with advantages in bioavailability and absorption. The present investigation intends to analyze the effects of conversion from IR-Tac to LCPT on phenotype and function of T-cells and B-cells.Methods16 kidney transplant patients treated by triple standard immunosuppression with a stable graft function undergoing a switch from IR-Tac to LCPT were included in this observational prospective study. We measured the main immune cell types and performed an in-depth characterization of B cell, dendritic cells and T cells including regulatory T cells of the patients before, 4 and 8 weeks after IR-Tac to LCPT conversion using multi-parameter fl ow cytometry. Additionally, we analyzed T cells by assessing third-party antigens (Tetanus Diphtheria, TD)-reactive T cells, which could be analyzed by restimulation with tetanus vaccine.ResultsOverall, we found no significant alterations following LCPT conversion for the most immune cell populations with a few cell populations showing transient quantitative increase. Thus, 4 weeks after conversion, more regulatory T cells could be measured in the patients with a significant shift from memory to naïve Tregs. Furthermore, we found a transient B cell expansion 4 weeks after conversion from IR-Tac to LCPT. There were no changes in the percentage of other basic immune cell types and the antigen-reactive T cells were also not altered after changing the medication to LCP-tacrolimus.ConclusionHere, we demonstrate first insights into the immune system changes occurred under IR-Tac to LCPT conversion therapy in kidney transplant patients. While phenotypic and functional characteristics of the most immune cell populations did not change, we could observe an a transient expansion of regulatory T cells in peripheral blood following IR-Tac to LCTP conversion, which might additionally contribute to the overall immunosuppressive effect.